The Unseen Archive of Idi Amin: Making History in a Tight Corner - Derek, R. Peterson; Richard, Vokes; Nelson, Abiti; Edgar, C. Taylor (Cambridge University Press, 2021)
In May 2019 we launched a special exhibition at the Uganda Museum in Kampala titled “The Unseen Archive of Idi Amin.” It consisted of 150 images made by government photographers in the 1970s. In this essay we explore how political history has been delimited in the Museum, and how these limitations shaped the exhibition we curated. From the time of its creation, the Museum's disparate and multifarious collections were exhibited as ethnographic specimens, stripped of historical context. Spatially and organizationally, “The Unseen Archive of Idi Amin” turned its back on the ethnographic architecture of the Uganda Museum. The transformation of these vivid, evocative, aesthetically appealing photographs into historical evidence of atrocity was intensely discomfiting. We have been obliged to organize the exhibition around categories that did not correspond with the logic of the photographic archive, with the architecture of the Museum, or with the experiences of the people who lived through the 1970s. The exhibition has made history, but not entirely in ways that we chose.
Keywords: Idi Amin,Uganda, heritage, museums, photographs, visuality